Social and Moral Practices of the Organizations and Employee-Based Brand Equity: Female Digital Labor Perspective - Hu, Sha (Frontiers in Psychology, 2022)
This study investigates the role of socially responsible management as a significant determining factor for employees’ morale engagement (EME), employee vitality (EV), and employee-based brand equity (EBBE). Human resource management policies and strategies are important for addressing the interests of the employees and boosting the overall effectiveness of the organization. To examine this, this study analyzes the role of socially responsible management and organizational morality on EME with the mediation of EV. Also, the study examines the role of EME in EBBE. To conduct this study, the data were obtained from 310 female employees working in software houses from home in China. The sampling technique used in the study is purposive sampling. A partial least square structural equation modeling technique is used to analyze the data of the study. The study found that socially responsible management has a positive effect on both EME and EV. The study also reveals that organizational morality has a positive impact on EME and consequently impacts the EBBE in a positive way. The results of the mediation analysis show that EV mediates the relationship between socially responsible management and EME. The study provides practical implications, explaining the strategies and policies that can be adopted by the HR department of the organization to boost employee interests. The study also provides some limitations and future recommendations, such as sample size, the context of the study, and adding new variables to the existing framework.